Sex Differences in Tolerance to Delta-9-Tetrahydrocannabinol in Mice With Cisplatin-Evoked Chronic Neuropathic Pain - Henderson-Redmond, Angela N.; Crawford, LaTaijah C.; Sepulveda, Diana E.; Hale, David E.; Lesperance, Julia J.; Morgan, Daniel J. (Frontiers in Molecular Biosciences, 2021)
Tolerance to the pain-relieving effects of cannabinoids limits the therapeutic potential of these drugs in patients with chronic pain. Recent preclinical research with rodents and clinical studies in humans has suggested important differences between males and females in the development of tolerance to cannabinoids. Our previous work found that male mice expressing a desensitization resistant form (S426A/S430A) of the type 1 cannabinoid receptor (CB1R) show delayed tolerance and increased sensitivity to the antinociceptive effects of delta-9-tetrahydrocannabinol (∆9-THC). Sex differences in tolerance have been reported in rodent models with females acquiring tolerance to ∆9-THC faster than males. However, it remains unknown whether the S426A/S430A mutation alters analgesic tolerance to ∆9-THC in mice with chemotherapy-evoked chronic neuropathic pain, and also whether this tolerance might be different between males and females. Male and female S426A/S430A mutant and wild-type littermates were made neuropathic using four once-weekly injections of 5 mg/kg cisplatin and subsequently assessed for tolerance to the anti-allodynic effects of 6 and/or 10 mg/kg ∆9-THC. Females acquired tolerance to the anti-allodynic effects of both 6 and 10 mg/kg ∆9-THC faster than males. In contrast, the S426A/S430A mutation did not alter tolerance to ∆9-THC in either male or female mice. The anti-allodynic effects of ∆9-THC were blocked following pretreatment with the CB1R antagonist, rimonabant, and partially blocked following pretreatment with the CB2R inverse agonist, SR144528. Our results show that disruption of the GRK/β-arrestin-2 pathway of desensitization did not affect sensitivity and/or tolerance to ∆9-THC in a chronic pain model of neuropathy.